Highlighting the Teachers’ Perception on Designing Comic Strip as English Teaching Media - Wicaksono, Bayu; Wardani, Agista; Khoiriyah, Khoiriyah (Asosiasi Lembaga Pendidikan Tenaga Kependidikan Perguruan Tinggi Muhammadiyah Aisyiyah, 2025)
The use of engaging instructional media is important in supporting effective English language teaching, particularly in improving students’ motivation and assisting teachers’ instructional practices. This community service program aimed to develop a student’s workbook using comic strips as ready-to-use teaching materials for English teachers and to evaluate teachers’ perceptions of its potential classroom use. The program was conducted in collaboration with a Muhammadiyah-affiliated secondary school and implemented through several stages, including needs analysis, topic selection, learning activity planning, material development, and evaluation. The evaluation involved 12 English teachers who participated in workshops introducing the developed workbook. A mixed-methods approach was employed to assess the outcomes of the program. Quantitative data were collected through a questionnaire using a five-point Likert scale, while qualitative data were obtained through an online Focus Group Discussion. The findings show that teachers had positive perceptions of the comic-based student’s workbook. All evaluated aspects obtained mean scores above 4.00, indicating strong agreement. Teachers perceived that the workbook could enhance students’ interest and engagement, clarify learning objectives, provide meaningful learning activities, and support English language skill development. From the teachers’ perspective, the workbook was considered practical, easy to use, and helpful in reducing lesson preparation time. Teachers also expressed comfort and intention to use the workbook in their future teaching. In conclusion, this community service program demonstrates that developing a comic-based student’s workbook is a feasible and effective approach to supporting teachers’ professional development and improving English language teaching practices.